Evaluating the regenerative efficacy of titanium-prepared platelet-rich fibrin in the treatment of gingival recession: a systematic review and meta-analysis: Т-ПРФ гингивална рецесија - Систематски преглед и мета-анализа - Gummaluri, Shiva Shankar; Gurumoorthy, Kaarthikeyan; Damera, Trinath Kishore; S S, Sai Karthikeyan; Pavan Kumar, Sandhya; Gidijala, Naven Vital Kumar (Vojnosanitetski pregled, 2025)
Background/Aim. Titanium-prepared platelet-rich fibrin (PRF) – T-PRF was considered a new platelet concentrate that is now frequently used in dentistry. The aim of this study was to examine T-PRF’s regenerative effectiveness in treating gingival recession (GR). Methods. The present study is a systematic review and meta-analysis. A comprehensive search was performed in PubMed, Scopus, Embase, Web of Science, Google Scholar, and Cochrane databases. Medical Subject Headings terms like ‘platelet-rich fibrin’, ‘platelets’, ‘gingival recession’, ‘titanium’, and ‘root coverage’ were used to identify the final included studies. Review Manager software was used to perform the statistical analysis. The value of p ≤ 0.05 was considered statistically significant. Results. A total of six studies were included in the systematic review, three of which qualified for meta-analysis. The systematic review suggested that T-PRF is a superior biomaterial in the treatment of GR and showed comparable results to those of the gold standard connective tissue graft (CTG). However, in the meta-analysis at six-month follow-up, for mean root coverage width, the combined effect size across three studies with 272 participants was a standardized mean difference of 0.07 (-0.17, 0.31), indicating no significant difference between the interventions. For mean root coverage depth, the combined effect size was 0.50 (-0.71, 1.70), also showing a non-significant trend favoring one intervention over the other. Conclusion. Within the limitations, the present systematic review suggests clinically improved outcomes with T-PRF. In contrast, the meta-analysis did not show any significant advantage of T-PRF over CTG or PRF.